Proteínas isoladas do látex de Himatanthus drasticus (Mart.) Plumel (Apocynaceae) protegem a mucosa gástrica de camundongos contra lesões induzidas por etanol : envolvimento da via NO/GMPc/KATP e da glutationa - Marques, Larisse Mota (2012)
The HdLP, a protein fraction isolated from the Himatanthus drasticus latex, known by the common name of Janaguba, was evaluated in the ethanol-induced gastric lesion model in rats. The HdLP (0.5, 5.0 and 50.0 mg/Kg) was administered IV 30 minutes before absolute ethanol (0.2 mL/animal, oral dose) and its gastroprotective effect was observed only at the 5.0 mg/Kg dose, which significantly (p<0.05) reduced the gastric lesions induced by ethanol by 83%, besides also significantly reducing the histopathological lesion scores. The gastroprotective mechanism of the HdLP was investigated at the 5.0 mg/Kg dose. The HdLP gastroprotective effect was inhibited in animals pretreated with L-NAME (20 mg/Kg, s.c.), a nonspecific NOS inhibitor, with glibenclamide (5 mg/Kg, IP), an ATP-sensitive potassium channel (KATP) blocking drug, or with ODQ (10 mg/Kg, IP), a guanylate cyclase selective inhibitor, and the lesion areas in these groups increased significantly (p<0.05) by 63%, 290% and 249%, respectively, compared with the group pretreated only with the fraction. The HdLP also induced an increase of NO in the gastric mucosa lesioned by ethanol. On the other hand, pretreating the animals with indomethacin (10 mg/Kg, oral dose), a nonspecific COX inhibitor, or with capsazepine (5 mg/Kg, IP), a TRPV1 receptor antagonist drug, did not inhibit the HdLP gastric protection in the experimental model. In addition, the pretreatment with HdLP significantly (p<0.05) re-established the NP-SH (glutathione) gastric levels which had been depleted by the ethanol. Therefore, the results show, through different mechanisms, that the HdLP exert a gastroprotective function, with the involvement of NO, cGMP, activation of the KATP channels and antioxidant action